(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Librarians are recognized for being early adopter’s technologies, but they’ve begun to use RFID to deliver more efficient as well as effective circulation services, as well as to protect library assets. Despite the fact that RFID adoption in libraries has increased significantly in recent years, the expense of the technology, the lack of standards, as well as privacy protection remain key hurdles to additional libraries adopting it. In terms of budgetary restrictions, if libraries adopt such technologies, the increases the quality of "Return on Investments" might be obtained, as it would speed up the circulating process by allowing employees to engage in the other user behavior. Libraries that wish to utilize RFID need to use ISO 28560 compatible RFID tags in combination to ISO 15693, ISO 18000-3, as well as other NISO-established worldwide guidelines due to the absence of standardization. Libraries should follow industry standards and keep no personal information on RFID tags to preserve users’ privacy. Whether or whether libraries utilize RFID technology now, they won’t be able to escape it in the future since book wholesalers offer publications which have already been identified for free. RFID is the newest technology used in library theft detection methods (Radio Frequency Identification). Apart from EM (Electro-Mechanical) and RF (Radio Frequency) systems, which have long been used in libraries, RFID-based systems go beyond security to be become traceability capable of integrating security with much more efficient resources monitoring all through the library, such as easier and quicker charge as well as discharge, inventory, and handling of materials.